Distribution and excretion of 2, 2′, 3, 4′, 5, 5′, 6-heptachlorobiphenyl (CB187) and its metabolites in rats and guinea pigs. (January 2015) - Ohta, Chiho; Haraguchi, Koichi; Kato, Yoshihisa; Endo, Tetsuya; Kimura, Osamu; Koga, Nobuyuki
Highlights: 4-OH-CB187 is found only in the blood not in the feces of animals. 4′-OH-CB178, a major metabolite of CB187, is easily excreted in the feces. Guinea pigs metabolize CB187 faster than do rats. Abstract: 4-Hydroxy (OH)-2, 2′, 3, 4′, 5, 5′, 6-heptachlorobiphenyl (CB187) is a polychlorinated biphenyl (PCB) metabolite present in human serum at the highest concentration of the PCB metabolites. Our previous study demonstrated that CB187 was metabolized by rat and guinea pig liver microsomes to the major metabolite 4′-OH-2, 2′, 3, 3′, 5, 5′, 6-heptachlorobiphenyl (CB178), and the two minor metabolites 4-OH-CB187 and 4′-OH-2, 2′, 3, 5, 5′, 6-hexachlorobiphenyl (CB151). In this study, the distribution of these metabolites in serum, liver and kidney, and their fecal excretion, were examined in rats and guinea pigs intraperitoneally dosed with CB187. Similarly to the in vitro study, 4′-OH-CB178 was a major metabolite in the liver, serum and feces of both animal species on day 4 after CB187 injection, and the level in the liver was about 20 times higher in untreated guinea pigs than in untreated rats. In addition, 4-OH-CB187, a minor metabolite, was detected in the serum and kidneys, but not in the feces, of both guinea pigs and rats. Another minor metabolite, 4′-OH-CB151, was detected at a lower level only in guinea pig feces; little was found in the serum or liver of either animals. Over the 30 d following CB187 injection into guinea pigs, 4′-OH-CB178 and 4-OH-CB187 in the serum was observed at higher level on day 4 and day 16 after injection, respectively. The majority of the 4′-OH-CB178 was rapidly excreted to the feces following unmetabolized CB187, whereas 4-OH-CB187 was not found in guinea pig feces and liver during 30 d. These results support previous reports that 4-OH-CB187 is retained persistently in animal blood.